Impact of the real economy on stock market performance: evidence from Arab countries - Hasseeb, Mariam (AUC Knowledge Fountain, 2015)
In this paper, the macroeconomic determinant of stock market performance represented in stock market capitalization in 15 markets in the Arab world are assessed. The analysis is based on panel data techniques from 1995 to 2014. Furthermore, differentiation between Arab countries according to their affiliation to the Gulf Cooperation Council (GCC) and according to their classification as oil vs. non-oil economies is explored, In addition to traditional variables, an institutional variable and remittances are included among the regressors. The results were that domestic credit, GDP, economic freedom and net remittances have negative effect on stock market capitalization. On the other hand, investment, stocks traded and inflation have a positive effect. Upon classifying the sample to oil vs. non-oil economies, domestic credit lost significance, GDP, economic freedom and net remittances have a negative effect in oil economies and a positive effect in non-oil economies. Inflation has a positive effect in oil economies and a negative effect in non-oil ones. Furthermore, classifying the sample to GCC vs. non-GCC countries, GDP has a negative effect on both. Stocks traded and investment have a positive effect on both. Domestic credit, net remittances and inflation have a negative effect in GCC countries and a positive one in non-GCC countries.